Modeling of electron localization in a quasi-one-dimensional tight-binding chain - Al-Seadi, S. A.; AbdulAlmohsin, Samir. M .; Ajeel, Sadeq Kh. (University of Thi-Qar Journal, 2019)
In this paper we propose general formula for the transmission probability for electron transfer through DNA molecules have been derived in the level of nanometers size , by assuming DNA molecules chain as nano wire. We studied localization properties for two DNA sequences: [(G/C)10] and [(A/T)10]. We have also investigated and focused on the transmission for the these two periodic ,and both at temperature degrees (0 and 300K).